PERAN PURNA PASUKAN PENGIBAR BENDERA PUSAKA INDONESIA DALAM MENGEMBANGKAN CIVIC VIRTUE SEBAGAI KARAKTERISTIK SMART AND GOOD CITIZEN - Arisandy, Desy (2016)
This research describes the role of the organization in developing a civic virtue as the characteristics of smart and good citizen. It is one of the goals of civic education The problem of this research are; What Form of activities carried in Bendera Pusaka Flag Hoisting Troop (BPFHT) of Indonesia in developing a civic virtue as the characteristics of smart and good citizen, What is the process of Indonesian BPFHT in developing civic virtue as the characteristics of smart and good citizen, What is the constraints of the board and members of Indonesian BPFHT in developing civic virtue as the characteristics of smart and good citizen. How do the results achieved as the ultimate goal in developing the impact of civic virtue as the characteristics of smart and good citizen. This study uses a Grand Theory of Character Education from Thomas Lickona and Civic Virtue from Aristotle. The approach used in this research is qualitative approach with the method of descriptive study. Data collection is through observation and interview. The findings of this study were (1) Activity form that implemented in Indonesian BPFHT in developing a civic virtue as the characteristics of smart and good citizen are Diklatsar, Desa Bahagia, Inaugural Members of Indonesian BPFHT, weekly Training of Trainers to successfully develop civic virtue members. (2) Indonesian BPFHT process in developing a civic virtue as the characteristics of smart and good citizen lasted for one year, only the chosen ones are mentally tough to meet the objectives of Indonesian BPFHT. (3) Full board and members obstacles of Indonesian BPFHT in developing a civic virtue as the characteristics of smart and good citizen are the attitude and decrease the motivation, decrease the commitment, cost problem and not dare to leaving the comfort zone (4) The results achieved as the ultimate goal in developing the impact of civic virtue as the characteristics of smart and good citizen are practicing Pancasila and comply with applicable laws in society, mentally tough, be fair and thoughtful, having a sense of community or family and, autonomous. ;---Penelitian ini menjelaskan peran organisasi dalam mengembangkan civic virtue sebagai karakteristik smart and good citizen, hal tersebut merupakan salah satu tujuan dari pendidikan kewarganegaraan. Rumusan masalah dalam penelitian ini adalah. Bentuk kegiatan apakah yang dilaksanakan Purna Paskibraka Indonesia dalam mengembangkan civic virtue sebagai karakteristik smart and good citizen, Bagaimanakah proses Purna Paskibraka Indonesia dalam mengembangkan civic virtue sebagai karakteristik smart and good citizen, Hal Apa saja yang menjadi kendala pengurus dan anggota Purna Paskibraka Indonesia dalam mengembangkan civic virtue sebagai karakteristik smart and good citizen. Bagaimanakah hasil yang dicapai sebagai tujuan akhir dampak dalam mengembangkan civic virtue sebagai karakteristik smart and good citizen. Penelitian ini menggunakan Grand Theory Pendidikan Karakter dari Thomas Lickona dan Civic Virtue dari Aristoteles. Pendekatan penelitian ini adalah kualitatif dengan metode studi deskriptif. Pengumpulan data dilakukan melalui observasi, studi dokumentasi, dan wawancara. Temuan penelitian ini adalah (1) Bentuk kegiatan yang dilaksanakan Purna Paskibraka Indonesia dalam mengembangkan civic virtue sebagai karakteristik smart and good citizen adalah DIKLATSAR, Desa Bahagia, Pelantikan Anggota Purna Paskibraka Indonesia, Training of Trainer dan Kumpulan Mingguan yang berhasil mengembangkan civic virtue para anggota. (2) Proses Purna Paskibraka Indonesia dalam mengembangkan civic virtue sebagai karakteristik smart and good citizen berlangsung kurang lebih selama satu tahun, hanya orang-orang terpilih yang bermental tangguh yang dapat memenuhi tujuan Purna Paskibraka Indonesia. (3) Kendala pengurus dan anggota Purna Paskibraka Indonesia dalam mengembangkan civic virtue sebagai karakteristik smart and good citizen adalah sikap, menurunnya motivasi,menurunnya komitmen, kendala biaya dan tidak berani keluar dari zona nyaman (4) hasil yang dicapai sebagai tujuan akhir dampak dalam mengembangkan civic virtue sebagai karakteristik smart and good citizen yaitu Mengamalkan Pancasila dan mematuhi hukum yang berlaku di masyarakat, bermental tangguh, bersikap adil dan bijaksana, Mempunyai rasa kebersamaan atau kekeluargaan dan Mandiri.